Citrullinated Histone H3 as a Therapeutic Target for Endotoxic Shock in Mice - Deng, Qiufang; Pan, Baihong; Alam, Hasan B.; Liang, Yingjian; Wu, Zhenyu; Liu, Baoling; Mor-Vaknin, Nirit; Duan, Xiuzhen; Williams, Aaron M.; Tian, Yuzi; Zhang, Justin; Li, Yongqing (Frontiers in Immunology, 2020)
Sepsis results in millions of deaths every year, with acute lung injury (ALI) being one of the leading causes of mortality in septic patients. As neutrophil extracellular traps (NETs) are abundant in sepsis, neutralizing components of NETs may be a useful strategy to improve outcomes of sepsis. Citrullinated histone H3 (CitH3) has been recently shown to be involved in the NET formation. In this study, we demonstrate that CitH3 damages human umbilical vein endothelial cells (HUVECs) and potentiates NET formation through a positive feedback mechanism. We developed a novel CitH3 monoclonal antibody to target peptidylarginine deiminase (PAD) 2 and PAD 4 generated CitH3. In a mouse model of lethal lipopolysaccharide (LPS) induced shock, neutralizing CitH3 with the newly-developed anti-CitH3 monoclonal antibody attenuates inflammatory responses, ameliorates ALI, and improves survival. Our study suggests that blocking PAD2- and PAD4-citrullinated histone H3 might be a potential therapeutic method for the treatment of sepsis.